Sustainable solid waste management from the perspective of policy / Haidy Henry Dusim, Mohammad Tahir Mapa and Delia L. Olaybal - Dusim, Haidy Henry; Mapa, Mohammad Tahir; Olaybal, Delia L. (Universiti Teknologi MARA, Shah Alam, 2016)
Traditionally, issues of solid waste management were mainly considered as technical issues and often analysed from the perspective of technology. However, based on the concepts of integrated sustainable solid waste management (ISWM), it is argued that issues of solid waste management is not purely technological, instead it is strongly influenced by the aspects of policy, social, economy, institutional and environment. In a developing country like Malaysia, policy plays an important driver to improve its solid waste management and this is clearly demonstrated when the government of Malaysia has recently introduced a mandatory household waste separation in Peninsular Malaysia starting from the 1st of September 2015. Therefore, the aim of this paper is to highlight the aspect of policy in the context of solid waste management. Previous study has shown that adequate policy played an important factor towards sustainable solid waste management. However, their study did not clearly explain the meaning of adequate policy and the important elements consisted under an adequate policy. Therefore, the purpose of this paper is to explore the meaning of an adequate policy and to identify the important elements consisted in an adequate policy. The findings of this study would be significant to be used as a guideline, especially for the local government to analyse whether they have an adequate policy or not as this information would guide the local government to develop more adequate policy in order to achieve more sustainable solid waste management.